Features of electron gas in InAs nanowires imposed by interplay between nanowire geometry, doping and surface states - V. E. Degtyarev (Nature Portfolio, 2017)
Abstract We present a study of electron gas properties in InAs nanowires determined by interaction between nanowire geometry, doping and surface states. The electron gas density and space distribution are calculated via self-consistent solution of coupled Schroedinger and Poisson equations in the nanowires with a hexagonal cross-section. We show that the density of surface states and the nanowire width define the spatial distribution of the electrons. Three configurations can be distinguished, namely the electrons are localized in the center of the wire, or they are arranged in a uniform tubular distribution, or finally in a tubular distribution with additional electron accumulation at the corners of the nanowire. The latter one is dominating for most experimentally obtained nanowires. N-type doping partly suppresses electron accumulation at the nanowire corners. The electron density calculated for both, various nanowire widths and different positions of the Fermi level at the nanowire surface, is compared with the experimental data for intrinsic InAs nanowires. Suitable agreement is obtained by assuming a Fermi level pinning at 60 to 100 meV above the conduction band edge, leading to a tubular electron distribution with accumulation along the corners of the nanowire.